Chapter 3 "Rights a di Plan" Sistren and sexual solidarities in Jamaica - Batra, Kanika (Taylor & Francis, 2021)
Chapter 3, "'Rights a di Plan': Sistren and Sexual Solidarities in Jamaica," focuses on the newsletter Sistren published by the Sistren Theatre Collectives in the Jamaica from the 1970s to the 1990s. The contents of the magazine reveal that while the women's movement advocated legislative reform to address rampant sexual violence, activists steered clear of making any direct connections with reproductive and sexual choice and orientations. Presenting these as health concerns enabled a detailed, though indirect, discussion on sexual choice within these magazines without inviting opprobrium either from the large readership or the governmental machinery in Jamaica and other Caribbean nation-states.